-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathshort_explanation
67 lines (52 loc) · 1.91 KB
/
short_explanation
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
degree(xi) = di
degree(F) = d
s = d1 + d2 + d3 + d4
Omega = d1 x1 d(x2) /\ d(x3) /\ d(x4)
- d2 x2 d(x3) /\ d(x4) /\ d(x1)
+ d3 x3 d(x4) /\ d(x1) /\ d(x2)
- d4 x4 d(x1) /\ d(x2) /\ d(x3)
= (x2 x3 x4)^(-d1+1) (x1)^(s-d1+1) d1^(-2)
d(x2^d1/x1^d2) /\ d(x3^d1/x1^d3) /\ d(x4^d1/x1^d4).
Eta = d1 x1 d(x2) /\ d(x3)
- d2 x2 d(x1) /\ d(x2)
+ d3 x3 d(x1) /\ d(x2)
= (x2 x3)^(-d1+1) (x1)^(d2+d3+1) d1^(-1)
d(x2^d1/x1^d2) /\ d(x3^d1/x1^d3).
We compute
d( G Eta / F^j )
= d(G) /\ Eta / F^j
+ G d(Eta) / F^j
- j G d(F) /\ Eta / F^(j+1)
= G_1 d(x1) /\ d1 x1 d(x2) /\ d(x3) / F^j
- G_2 d(x2) /\ d2 x2 d(x1) /\ d(x3) / F^j
+ G_3 d(x3) /\ d3 x3 d(x1) /\ d(x2) / F^j
+ G_4 d(x4) /\ Eta / F^j
+ (s-d4) G d(x1) /\ d(x2) /\ d(x3) / F^j
- j G F_1 d(x1) /\ d1 x1 d(x2) /\ d(x3) / F^(j+1)
- j G F_2 d(x2) /\ d2 x2 d(x3) /\ d(x1) / F^(j+1)
- j G F_3 d(x3) /\ d3 x3 d(x1) /\ d(x2) / F^(j+1)
- j G F_4 d(x4) /\ Eta / F^(j+1)
= [(degree(G)+s-d4)G - d4 x4 G_4] d(x1) /\ d(x2) /\ d(x3) / F^j
+ G_4 d(x4) /\ Eta / F^j
- j G[degree(F) F - d4 x4 F_4 ] d(x1) /\ d(x2) /\ d(x3) / F^(j+1)
- j G F_4 d(x4) /\ Eta / F^(j+1)
(*) = - d4 x4 G_4 d(x1) /\ d(x2) /\ d(x3) / F^j
+ G_4 d(x4) /\ Eta / F^j
+ j d4 G x4 F_4 d(x1) /\ d(x2) /\ d(x3) / F^(j+1)
- j G F_4 d(x4) /\ Eta / F^(j+1)
= G_4 Omega / F^j - j G F_4 Omega / F^(j+1)
(*) Note that: degree(G) = j degree(F) - s + d4
Also note that the degree of GF_4 is equal to (j+1)d-s.
The forms where cohomology lies are
h Omega / F , h Omega / F^2 , h Omega / F^3
We define Delta by the formula
Delta = (F^p - sigma(F))/p
where sigma is the lift of frobenius mapping xi to xi^p. So the Frobenius maps
sigma( h Omega / F^j ) =
sigma(h) p^3 (x1x2x3x4)^(p-1) Omega
-----------------------------------
(F^p - p Delta)^j
=
\sum_{i=0}^infty
p^i Delta^i sigma(h) p^3 (x1x2x3x4)^(p-1) (i+j-1 choose j-1)
Omega / F^(p(j+i))